Sexual Orientation and Childhood Gender Nonconformity: Evidence from Home Videos - Rieger, Gerulf; Linsenmeier, Joan A. W; Gygax, Lorenz; Bailey, J. Michael (Developmental psychology, 2008)
Homosexual adults tend to be more gender nonconforming than heterosexual adults in some of their behaviors, feelings, and interests. Retrospective studies have also shown large differences in childhood gender nonconformity, but these studies have been criticized for possible memory biases. The authors studied an indicator of childhood gender nonconformity not subject to such biases: childhood home videos. They recruited homosexual and heterosexual men and women (targets) with videos from their childhood and subsequently asked heterosexual and homosexual raters to judge the gender nonconformity of the targets from both the childhood videos and adult videos made for the study. Prehomosexual children were judged more gender nonconforming, on average, than preheterosexual children, and this pattern obtained for both men and women. This difference emerged early, carried into adulthood, and was consistent with self-report. In addition, targets who were more gender nonconforming tended to recall more childhood rejection.